It is neither.
To be even, f(x) must equal f(-x).
If you substitute -x for x, you'd get
y = (-x)^2 - 2(-x) -8
y = x^2 +2x -8
This is not the same as the original, so this is not even.
To be odd, f(x) must equal -f(-x).
If you take the -x substitution from the last step and then multiply it by -1, you'd have:
y = -1 (x^2 +2x -8)
y = -x^2 -2x +8
This is not the same as the original either.
The function is neither even nor odd.
Answer:
c = 127°
Step-by-step explanation:
∡c and ∡a are supplementary angles.
Supplementary angles sum 180°
∡a = 53°
Then:
53° + c = 180°
c = 180° - 53°
c = 127°
Answer:
Q = 146
Step-by-step explanation:
We know that angle S and T are equal because the sides are equal
The measure of the exterior angle is equal to the sum of the opposite interior angles in a triangle
Q = S+T
Q = S+S
Q = 2S
Q =2* 73
Q = 146